2019
DOI: 10.1177/0269881119875976
|View full text |Cite
|
Sign up to set email alerts
|

The mGluR2/3 agonist LY379268 reverses NMDA receptor antagonist effects on cortical gamma oscillations and phase coherence, but not working memory impairments, in mice

Abstract: Background: Abnormalities in neural oscillations that occur in the gamma frequency range (30–80 Hz) may underlie cognitive deficits in schizophrenia. Both cognitive impairments and gamma oscillatory disturbances can be induced in healthy people and rodents by administration of N-methyl-D-aspartate receptor (NMDAr) antagonists. Aims: We studied relationships between cognitive impairment and gamma abnormalities following NMDAr antagonism, and attempted to reverse deficits with the metabotropic glutamate receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 78 publications
1
22
2
Order By: Relevance
“…To elucidate the etiology and pathogenesis of schizophrenia, NMDA receptor antagonists including MK-801 and phencyclidine have been used to induce pharmacological animal models of schizophrenia ( 33 ). Consistent with previous studies that presented schizophrenia-like behaviors in the MK-801 injected animals ( 12 , 13 , 34 ), MK-801 administrated mice demonstrated the increase of locomotor activity, spatial working memory impairment and sensorimotor gating deficit. Quetiapine, an atypical antipsychotic drug, has been widely used in the treatment of schizophrenia and has shown its efficacy in treating positive and negative symptoms, as well as cognitive impairment in schizophrenia patients ( 14 16 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To elucidate the etiology and pathogenesis of schizophrenia, NMDA receptor antagonists including MK-801 and phencyclidine have been used to induce pharmacological animal models of schizophrenia ( 33 ). Consistent with previous studies that presented schizophrenia-like behaviors in the MK-801 injected animals ( 12 , 13 , 34 ), MK-801 administrated mice demonstrated the increase of locomotor activity, spatial working memory impairment and sensorimotor gating deficit. Quetiapine, an atypical antipsychotic drug, has been widely used in the treatment of schizophrenia and has shown its efficacy in treating positive and negative symptoms, as well as cognitive impairment in schizophrenia patients ( 14 16 ).…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study has shown phencyclidine, an NMDA receptor antagonist, induced brain demyelination when administrated in postnatal rats ( 11 ). MK-801, another NMDA receptor antagonist, can cause schizophrenia-like behaviors including prepulse inhibition (PPI) deficit and memory impairment in animals, and is used as a pharmacological model of schizophrenia ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies on mGluR3 and mGluR2 knockout mice demonstrated that mGluR2, but not mGluR3, mediated the effects of LY379268 in experimental models predictive of antipsychotic activity [71]. LY379268 also showed promising effects in other schizophrenia models based on pharmacological blockage of NMDA receptor (ketamine and MK-801) [87] but had a marginal effect on amphetamine (AMPH)-induced hyperlocomotion in rats [72]. These results demonstrate the specificity of mGluR2/3 agonists toward glutamatergic signaling without any effects on the dopamine system.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Given that antipsychotic drugs are administered chronically, it is unknown whether the acute effects of novel substances reported in animal studies will also be seen in clinical practice or their long-term use will result in tolerance. Furthermore, it must be considered that mGluR2/3 agonists, although successfully reversing some cognitive effects in NMDA receptor hypofunction models [63,87,88], have no effect or impair cognition in healthy animals [76]. This implies that the therapeutic use of mGluR2/3 agonists may be limited to the conditions of NMDA receptor dysfunction or have difference efficacy depends on the disease state.…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…The activation of glutamate metabotropic receptors has been studied as a novel mechanism to improve cognitive deficit in schizophrenia because the activation of metabotropic receptors reduces the release of glutamate in cortical neurons, which, as exposed above, is paradoxically augmented in schizophrenia [ 181 ]. Results in mice are contradictory because a clear benefit was observed in some studies, while other studies failed to show a benefit of activating metabotropic receptors on cognitive deficit [ 182 , 183 ]. This lack of efficacy was also observed in clinical trials with LY2140023 [ 112 ].…”
Section: Treatment Of Cognitive Deficit In Schizophreniamentioning
confidence: 99%